AB0852 Imaging of Infectious Spondylo Discitis in Tunisia. (10th June 2014) - Slouma, M.; Ben Abdelghani, K.; Souabni, L.; Kassab, S.; Chekili, S.; Laatar, A.; Zakraoui, L.
Abstract : Background: Infectious spondylodiscitis remains an important cause of morbidity and mortality in Tunisia. Clinical presentation may be insidious with unremarkable initial radiographs providing false reassurance. MR imaging is considered as the imaging technique of choice in infectious spondylodiscitis. Objectives: The aim of this study was to provide an overview of the radiological features of infectious spondylodiscitis. Methods: A retrospective study effectuated in the department of Rheumatology in Tunisia between 1995 and 2013. We included all patients with infectious spondylodiscitis. Results: Forty one patients were included. There were 21 males and 20 females. The mean age was 61.66 years, ranged from 25 to 89 years. Duration of symptoms varied from 20 to 90 days. All patients presented with back pain. Fever was noted in 38 cases. A neurological deficit was noted in 7 patients. Inflammation tests were disturbed in 87% of cases (n=36). Spondylodiscites was suspected according to X-ray findings in 39 cases, showing disc space narrowing and irregularity of the end-plates. It was normal in 2 cases in which the duration of symptoms was 20 days in the first case and one month in the second case. The diagnosis was then confirmed by Disco-vertebral biopsy showing a pyogenic infection. MR imaging was performed in only 27 patients and had showed epiduritis in 12 patients and paravertebral abscess in 8 patients. CT- guided disco vertebral biopsy was performed in 36 patients leading to the diagnosis in 22 cases. The Lumbar region was the most common affected (58%) followed by dorsal spine (32%) and cervical spine (10%). A multi-stage spondylodiscitis was found in 4 cases. Pyogenic Spondylodiscitis was associated with a septic arthritis in one case. Spinal Tuberculosis was complicated by hepatic tuberculoma in one case. All patients underwent initially adapted antibiotics and immobilization leading to recovery in 73% of cases (n=30). Seven patients were lost during follow up. Neurological complication occurred in 3 cases and sepsis in 1 case. Conclusions: MR imaging had greatly contributed to prompt diagnosis, thus allowing implementation of timely appropriate treatment, indeed in patient with normal spine X-ray. In our study, MR imaging revealed epiduritis and paravertebral abscesses which still frequent in our country. The importance of whole spine imaging should be also underlined especially in case of multifocal infectious spondylodiscitis. References: Leone A, Dell'Atti C, Magarelli N, Colelli P, Balanika A, Casale R, Bonomo L. Imaging of spondylodiscitis. Eur Rev Med Pharmacol Sci 2012;16:8-19. An HS, Seldomridge JA. Spinal infections: diagnostic tests and imaging studies. Clin Orthop Relat Res 2006;444:27-33. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5561